Efektifitas Edukasi Terpadu Dalam Meningkatkan Efikasi Diri Pasien Pasca Operasi Total Hip dan Knee Replacement di Rumah Sakit - Muhajirin Maliga; Elly Lilianty Sjattar; Syahrul Syahrul (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2019)
ABSTRACT The research aimed ti investigate the effectiveness of the integrated education in improving the self-efficacy of the patients post opeation of the replacements of the hip and knee joints.In the research the search was carried out using the following databases: PubMed, Google Scholar, ProQuest and Science Direct. The next step was a secondary search based on the reference to the primary search results. There were 9articles so that the total  inclusion of 16 articles. The research results obtained after the intervention revealed that the participants of the education empowerment group showed significantly higher self-care competence and self-efficacy. Thus after giving an integrated educational intervention, there was an increase in the self-efficacyof the patients. It could be seen that were was an influence of the intervention on the increase of the self-efficacy of the patients after the operationsof replacemnt of the hip and knee joints. Key words: Integrated education, self-efficacy, Total Hip and Knee Replacement